Supporter Ownership as Entrepreneurship in American Soccer - Zachary T. Smith; R. Ethan Smith (Journal of Applied Sports Management, 2019)
Entrepreneurship has been touted as a crucial lens for the future of sports management scholarship (Hardy, 1996; Ratten, 2011). Ratten (2011a) specifically proposed sport entrepreneurship “as a category of entrepreneurship that fosters economic development in the sports management field” (p. 60). Yet, to date, no scholarly literature has applied the sports-entrepreneurship lens to local football (soccer) clubs in the United States. Thus, the purpose of this article is to use the lens of sport entrepreneurship to introduce the phenomenon of supporter owned football clubs in the United States (U.S.). Through the course of this article, sport entrepreneurship will be used not only as a conceptual framework for understanding supporter-ownership (SO) in the U.S., but also as a way to demonstrate that SO introduces unique practical issues of law, policy, and governance to the management of football in the U.S. Subscribe to JASM
Keywords: Fan ownership; football governance; soccer management; sport entrepreneruship; supporter ownership